Socialist Republic of Vietnam - Results-Based National Urban Development Program in the Northern Mountains Region : Fiduciary System Assessment - World Bank (Washington, DC, 2014)
The proposed Results-Based National Urban Development Program in the Northern Mountains Region (RBNUDP-NM or the Program ) will assist the Government of Vietnam in developing the implementation framework for its national urban program. It will do this by piloting a performance-based transfer system that will provide participating cities with a combination of much needed resources along with a clarification of implementation responsibilities, a results-based orientation, improved planning and a strengthening of oversight and accountability through audits and verification activities. The Program Development Objective is to strengthen the capacity of participating Northern Mountains cities to plan, implement and sustain urban infrastructure. The World Bank s Program-for-Results lending instrument is to be used for this operation. The Program targets the following seven cities Dien Bien Phu, Bac Kan, Cao Bang, Thai Nguyen, Hoa Binh, Tuyen Quang and Yen Bai.